Preparation method and application of catalytic membrane based on monatomic iron-manganese oxide

By depositing a single-atom iron-manganese oxide catalytic film on the ceramic film substrate and combining the technology of activated persulfate, the problem of F-53B in chrome plating wastewater is solved, especially when coexisting with PAM, it is realized. Efficient F-53B degradation and PAM interception improve the effect of wastewater treatment.

CN119488922AActive Publication Date: 2025-02-21SHANDONG JIANZHU UNIV

Patent Information

Application Number
CN202411880722.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-21
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The chromium mist inhibitor F-53B in chrome-plated wastewater is difficult to degrade, and the degradation rate decreases significantly when coexisting with PAM, resulting in a potential threat to the ecological environment and human health.

Method used

Using the preparation method based on single-atom iron-manganese oxide catalytic film, a catalytic film with a nanopore structure is deposited on the ceramic membrane substrate through the technology of combining interfacial deposition and calcination, and combined with activated persulfate (PMS) production activity Species, improve the degradation efficiency of F-53B.

Benefits of technology

The efficient degradation rate of F-53B is achieved, reaching 89.7%, and the PAM is effectively intercepted through the high-porosity catalytic film, reducing its interference with degradation, and significantly improving the efficiency of chrome plating wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488922A_ABST
    Figure CN119488922A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a catalytic membrane based on monatomic iron-manganese oxide, and belongs to the field of catalytic membrane water treatment. The invention aims to solve the problems that a chromium fog inhibitor F-53B in the existing chromium plating wastewater is difficult to degrade, and the degradation rate is greatly reduced when residual PAM and F-53B coexist. The method comprises the following steps: 1, preparing a casting solution; 2, dripping the membrane casting solution into pores of a hollow ceramic membrane substrate and drying; 3, preparing a potassium ferricyanide aqueous phase solution; 4, preparing a manganese acetylacetonate oil phase solution; and 5, dipping the dispensed ceramic membrane substrate in a potassium ferricyanide water-phase solution, dropwise adding a manganese acetylacetonate oil-phase solution into pores of the ceramic membrane substrate subjected to water-phase treatment, and finally calcining. The application comprises the following steps: degrading chlorinated polyfluoroalkyl ether sulfonate; or in the presence of polyacrylamide, the catalyst is used for degrading the chlorinated polyfluoroalkyl ether sulfonate. The preparation method is used for preparation and application of the catalytic membrane based on the monatomic iron-manganese oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic membrane water treatment. Background Art

[0002] Chrome plating is a commonly used surface treatment technology that deposits a thin and hard chromium layer on the metal surface to improve the wear resistance, aesthetics and service life of the workpiece. The chrome plating process is widely used, including electronics, automobiles, machinery and other fields. During the operation of the chrome plating process, the electroplating power causes a large amount of hydrogen and oxygen to be generated at the cathode and anode respectively. When these gases rise to the liquid surface in the form of bubbles and are released into the air, they carry a large amount of chromium-containing liquid to form mist pollutants, which is chromium mist. In order to prevent the harm of chromium mist to human body and environment, a chloropolyfluoroalkyl ether sulfonate (F-53B) is usually used as a chromium mist inhibitor to inhibit the escape of chromium mist. In addition, in the process of removing chromium from chrome plating wastewater, chemical reduction method is often used to remove residual Cr 6+ Reduction to Cr 3+ Calcium hydroxide is then added to form Cr(OH)3 precipitation, and then macromolecular organic flocculants such as polyacrylamide (PAM) and polyaluminium chloride (PAC) are added to flocculate the chromium hydroxide produced in the chromium removal process. However, after chromium removal from chromium plating wastewater, there are still residual chromium mist inhibitors and macromolecular organic substances such as PAM, which are extremely harmful to the ecological environment and humans.

[0003] As a perfluorinated compound, F-53B has a very strong CF bond that is difficult to break and is very difficult to degrade. Conventional treatment technologies mainly include adsorption and advanced oxidation technology, and the treatment efficiency is relatively low. Especially when PAM and F-53B coexist, PAM will interfere with the adsorption sites of the adsorbent or the degradation of F-53B by active oxygen produced by advanced oxidation technology, resulting in low treatment efficiency. Summary of the invention

[0004] The present invention aims to solve the problem that the chromium mist inhibitor F-53B in the existing chromium plating wastewater is difficult to degrade and the degradation rate will be greatly reduced when the residual PAM and F-53B coexist, and further provide a preparation method based on single-atom iron-manganese oxide catalytic film and its application.

[0005] A method for preparing a catalytic film based on single-atom iron-manganese oxide is carried out according to the following steps:

[0006] 1. Dissolve polyvinyl alcohol in ultrapure water, add Al2O3, TiO2 and dispersant to the polyvinyl alcohol solution, then ball mill, and finally vacuum degas to obtain a casting solution;

[0007] 2. dripping the casting liquid into the pores of the hollow ceramic membrane substrate and drying it, and then repeating the dripping and drying to obtain a ceramic membrane substrate after drip coating;

[0008] 3. dissolving potassium ferrocyanide in ultrapure water to obtain a potassium ferrocyanide aqueous solution;

[0009] 4. dissolving manganese acetylacetonate in n-hexane to obtain manganese acetylacetonate oil phase solution;

[0010] 5. Immerse the ceramic membrane substrate after drop coating in a potassium ferrocyanide aqueous solution, then take out the ceramic membrane substrate after water phase treatment, drop the acetylacetonate manganese oil phase solution into the pores of the ceramic membrane substrate after water phase treatment to carry out interfacial synthesis reaction, and then dry to obtain the ceramic membrane substrate after water phase and oil phase treatment, calcine the ceramic membrane substrate after water phase and oil phase treatment under nitrogen protection, and finally naturally cool to room temperature, thus completing the preparation method based on single atom iron-manganese oxide catalytic membrane.

[0011] The invention discloses an application of a catalytic membrane based on single-atom iron-manganese oxide, which is used for the degradation of chloropolyfluoroalkyl ether sulfonate; or for the degradation of chloropolyfluoroalkyl ether sulfonate in the presence of polyacrylamide.

[0012] The beneficial effects of the present invention are:

[0013] (1) The present invention utilizes a preparation method combining interface deposition and calcination to deposit a layer of single-atom iron-manganese oxide (FeO) on a macroporous hollow ceramic membrane substrate. 0.099 (MnO) 0.901 The catalyst membrane has a nanoporous structure. The catalyst membrane has high porosity and a high active site distribution. Through cross-flow filtration, the trapped particles are continuously removed from the surface of the ceramic membrane without remaining in the form of filter cake, thereby achieving continuous high flux. The operation process of the invention is simple and easy, and the required raw materials are easy to obtain.

[0014] (2) In the preparation process of the present invention, due to the high porosity of the nanoporous structure of the catalytic membrane, the pure water flux is 260L . m -2 . h -1 . bar -1 , so that the interception rate of the catalytic membrane to the flocculant PAM reaches 92.1%. Compared with the traditional membrane filtration technology (the interception rate is 70% to 80%), the interception rate of the catalytic membrane of the present invention is increased by 20% to 30%, and the interception effect is better.

[0015] (3) In the process of preparing the catalytic film of the present invention, due to calcination, the cyanide (C≡N) ligand decomposes and reacts with the lattice water and adsorbed water in the Prussian blue-like film to produce carbon and nitrogen oxide gases that volatilize, thereby forming (FeO) 0.099 (MnO) 0.901Single-atom oxide structure. Compared with traditional advanced oxidation technology (degradation rate of 60%-70%), the confinement effect of the nanopore structure of the catalytic membrane and the distribution of highly active sites enable the degradation rate of the chromium mist inhibitor to reach 89.7%.

[0016] (4) The present invention proposes a short-process catalytic membrane technology for treating chromium plating wastewater, which can efficiently intercept PAM, reduce the interference of PAM on the degradation of chromium mist inhibitor, and increase the degradation rate of F-53B from 48.3% to 89.7% by activating peroxymonosulfate (PMS) to produce active species. The present invention is a highly efficient membrane water treatment technology.

[0017] The invention is used for a preparation method based on a single-atom iron-manganese oxide catalytic film and its application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the formation of an iron-manganese Prussian blue analog precursor by interfacial polymerization of a catalytic membrane in Example 1;

[0019] Figure 2 This is a flow chart of the short-process chromium plating wastewater treatment based on the single-atom iron-manganese oxide catalytic membrane in Example 2;

[0020] Figure 3 This is a physical picture of the single-atom iron-manganese oxide catalyst film prepared in step five of Example 1;

[0021] Figure 4 are SEM images, (a) is the ceramic membrane substrate after drop coating prepared in step 2 of Example 1, (b) is a local enlarged view of (a), (c) is the single-atom iron-manganese oxide-based catalytic membrane prepared in step 5 of Example 1, and (d) is a local enlarged view of (c);

[0022] Figure 5 XRD diagrams of the single-atom iron-manganese oxide catalytic films prepared in Example 1 and Comparative Experiment 2;

[0023] Figure 6 The molecular structure diagram of the single-atom iron-manganese oxide catalytic film prepared in step 5 of Example 1;

[0024] Figure 7 This is a comparison chart of the pure water flux based on the single-atom iron-manganese oxide catalytic membrane prepared by Example 1 and Comparative Experiment 1 and the PAM rejection rate for chromium plating wastewater treatment in Example 2;

[0025] Figure 8 This is a comparison chart of the degradation efficiency of F-53B in chromium plating wastewater treatment using the single-atom iron-manganese oxide catalytic membrane prepared in Example 1 and Comparative Experiment 2 in Example 2;

[0026] Fig. 9 It is a comparison chart of the removal rates of short-process chromium plating wastewater treatment using the single-atom iron-manganese oxide catalytic membrane prepared in Example 1 in Example 2 and Example 3 and short-process chromium plating wastewater treatment in Comparative Experiment 3;

[0027] Fig.10 In Example 2 and Comparative Experiment 4, the hollow ceramic catalytic membrane prepared in Example 1 was used to treat chromium plating wastewater, and the effect of different concentrations of permonosulfate (PMS) on the degradation efficiency of the catalytic membrane was investigated. DETAILED DESCRIPTION

[0028] Specific implementation method 1: This implementation method is a method for preparing a single-atom iron-manganese oxide catalyst film, which is carried out according to the following steps:

[0029] 1. Dissolve polyvinyl alcohol in ultrapure water, add Al2O3, TiO2 and dispersant to the polyvinyl alcohol solution, then ball mill, and finally vacuum degas to obtain a casting solution;

[0030] 2. dripping the casting liquid into the pores of the hollow ceramic membrane substrate and drying it, and then repeating the dripping and drying to obtain a ceramic membrane substrate after drip coating;

[0031] 3. dissolving potassium ferrocyanide in ultrapure water to obtain a potassium ferrocyanide aqueous solution;

[0032] 4. dissolving manganese acetylacetonate in n-hexane to obtain manganese acetylacetonate oil phase solution;

[0033] 5. Immerse the ceramic membrane substrate after drop coating in a potassium ferrocyanide aqueous solution, then take out the ceramic membrane substrate after water phase treatment, drop the acetylacetonate manganese oil phase solution into the pores of the ceramic membrane substrate after water phase treatment to carry out interfacial synthesis reaction, and then dry to obtain the ceramic membrane substrate after water phase and oil phase treatment, calcine the ceramic membrane substrate after water phase and oil phase treatment under nitrogen protection, and finally naturally cool to room temperature, thus completing the preparation method based on single atom iron-manganese oxide catalytic membrane.

[0034] Principle: In order to ensure the efficient treatment of chrome plating wastewater, the present invention adopts a short-process technology based on single-atom iron-manganese oxide catalytic membrane. An Fe-Mn Prussian blue-like film with a Prussian blue-like structure is constructed on the inner surface of the pores of the ceramic membrane substrate by interfacial deposition. Its unique Fe-C≡N-Mn structure facilitates the uniform dispersion of Fe and Mn atoms. Calcination in a nitrogen atmosphere avoids excessive oxidation of Fe and Mn atoms. At the same time, the cyanide (C≡N) ligand decomposes and reacts with the lattice water and adsorbed water in the Prussian blue-like film to produce carbon and nitrogen oxide gases that volatilize, thereby forming (FeO) 0.099 (MnO) 0.901In addition, the dense Fe-Mn Prussian blue film forms a nanoporous structure due to the phase transformation and shrinkage of the grains during the sintering process.

[0035] Monatomic Iron-Manganese Oxide (FeO) 0.099 (MnO) 0.901 The Fe site transfers electrons to PMS, activating PMS to produce the main 1 O2 and high-valent iron oxide active substances. An oxidation reaction occurs between the active species and F-53B, and F-53B is gradually degraded and mineralized. The nanoporous structure of the film provides a guarantee for the effective interception and separation of macromolecular substances such as PAM, thereby reducing the negative impact of PAM and other substances on the degradation of F-53B. In addition, the nanopores of the catalytic membrane limit the diffusion space of the active species in the pores, thereby strengthening the contact between the active species and F-53B, and further improving the degradation efficiency of F-53B.

[0036] Catalytic membrane technology combines membrane separation and in-situ catalytic processes. It can first intercept PAM and then degrade F-53B in situ, thereby eliminating the negative impact of the coexistence of PAM and F-53B on the degradation of F-53B, and simultaneously achieve efficient removal of PAM and F-53B.

[0037] The beneficial effects of this embodiment are:

[0038] (1) This embodiment uses a preparation method combining interface deposition and calcination to deposit a layer of single-atom iron-manganese oxide (FeO) on a macroporous hollow ceramic membrane substrate. 0.099 (MnO) 0.901 And a catalytic membrane with a nanoporous structure. This catalytic membrane has high porosity and a high active site distribution. Through the form of cross-flow filtration, the trapped particles are continuously removed from the surface of the ceramic membrane without remaining in the form of filter cake, thereby achieving continuous high flux. The operation process of this embodiment is simple and easy, and the required raw materials are easy to obtain.

[0039] (2) In the preparation process of this embodiment, due to the high porosity of the nanoporous structure of the catalytic membrane, the pure water flux is 260L . m -2 . h -1 . bar -1 , so that the interception rate of the catalytic membrane to the flocculant PAM reaches 92.1%. Compared with the traditional membrane filtration technology (rejection rate is 70% to 80%), the interception rate of the catalytic membrane in this embodiment is increased by 20% to 30%, and the interception effect is better.

[0040] (3) In the process of preparing the catalytic film in this embodiment, due to calcination, the cyanide (C≡N) ligand decomposes and reacts with the lattice water and adsorbed water in the Prussian blue-like film to produce carbon and nitrogen oxide gases that volatilize, thereby forming (FeO) 0.099 (MnO) 0.901 Single-atom oxide structure. Compared with traditional advanced oxidation technology (degradation rate of 60%-70%), the confinement effect of the nanopore structure of the catalytic membrane and the distribution of highly active sites enable the degradation rate of the chromium mist inhibitor to reach 89.7%.

[0041] (4) This embodiment proposes a short-process catalytic membrane technology for treating chromium plating wastewater, which can efficiently intercept PAM, reduce the interference of PAM on the degradation of chromium mist inhibitor, and increase the degradation rate of F-53B from 48.3% to 89.7% by activating peroxymonosulfate (PMS) to produce active species. This embodiment is a highly efficient membrane water treatment technology.

[0042] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the mass ratio of polyvinyl alcohol to ultrapure water in step 1 is 1:(20-30); the mass ratio of polyvinyl alcohol to Al2O3 in step 1 is 1:(50-60); the mass ratio of polyvinyl alcohol to TiO2 in step 1 is 1:(20-30); the mass ratio of polyvinyl alcohol to dispersant in step 1 is 1:(15-30). Others are the same as specific implementation method 1.

[0043] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the particle size of Al2O3 in step 1 is 0.3 μm to 5 μm; the particle size of TiO2 in step 1 is 200 nm to 300 nm. Other aspects are the same as specific implementation method 1 or 2.

[0044] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1, polyvinyl alcohol is dissolved in ultrapure water at a temperature of 70°C to 80°C and a rotation speed of 100rpm to 200rpm, Al2O3, TiO2 and a dispersant are added to the polyvinyl alcohol solution, and then ball milling is performed for 4h to 5h at a ball-to-material mass ratio of 1:(0.2 to 0.3) and a rotation speed of 100rpm to 200rpm, and finally vacuum degassing is performed for 10min to 20min. Other steps are the same as those of specific embodiments 1 to 3.

[0045] Specific embodiment 5: This embodiment differs from any one of specific embodiments 1 to 4 in that: in step 2, the casting liquid is dripped into the pores of the hollow ceramic membrane substrate, and then dried at a temperature of 45°C to 55°C for 120s to 180s, and then the dripping and drying are repeated 2 to 3 times; the ratio of the dripping volume of the casting liquid described in step 2 to the area of ​​the inner surface of the pores of the hollow ceramic membrane substrate is (2 to 3) μL: 2mm 2 The pore diameter of the hollow ceramic membrane substrate described in step 2 is 5 micrometers to 8 micrometers. The rest is the same as the specific embodiments 1 to 4.

[0046] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: in step 3, potassium ferrocyanide is added to ultrapure water, and then stirred and dissolved for 5 min to 10 min at a temperature of 20°C to 30°C and a rotation speed of 200 pm to 400 rpm to obtain a potassium ferrocyanide aqueous solution; the concentration of the potassium ferrocyanide aqueous solution is 40 mM to 50 mM. The rest is the same as specific embodiments 1 to 5.

[0047] Specific embodiment 7: This embodiment is different from Specific embodiments 1 to 6 in that: in step 4, manganese acetylacetonate is added to n-hexane, and then water bath ultrasonication is performed for 20 min to 30 min at a temperature of 40° C. to 50° C. and a power of 120 W to 240 W to obtain a manganese acetylacetonate oil phase solution; the concentration of the obtained manganese acetylacetonate oil phase solution is 20 mM to 30 mM. The rest is the same as Specific embodiments 1 to 6.

[0048] Specific embodiment eight: This embodiment differs from any one of specific embodiments one to seven in that: in step five, the ceramic membrane substrate after drop coating is immersed in a potassium ferrocyanide aqueous solution for 30 min to 60 min at a shaking table speed of 150 rpm to 200 rpm, and then the ceramic membrane substrate after water phase treatment is taken out, and the acetylacetone manganese oil phase solution is dropped into the pores of the ceramic membrane substrate after water phase treatment, and the interface synthesis reaction is carried out for 30 min to 60 min at a shaking table speed of 100 rpm to 200 rpm, and then dried to obtain a ceramic membrane substrate after water phase and oil phase treatment; the ratio of the drop volume of the acetylacetone manganese oil phase solution described in step five to the area of ​​the inner surface of the pores of the hollow ceramic membrane substrate is (3 to 4) μL: 2 mm 2 The calcination in step 5 is specifically carried out under nitrogen atmosphere, heating to 500°C to 700°C at a rate of 5°C / min to 10°C / min, and then calcining at 500°C to 700°C for 1h to 2h. The rest is the same as the specific embodiments 1 to 7.

[0049] Specific implementation method 9: This implementation method is an application based on a single-atom iron-manganese oxide catalytic membrane, which is used to degrade chloropolyfluoroalkyl ether sulfonates; or when polyacrylamide is present, it is used to degrade chloropolyfluoroalkyl ether sulfonates.

[0050] Specific embodiment 10: This embodiment is different from specific embodiment 9 in that it uses cross-flow filtration to activate peroxymonosulfate to generate active species for degradation. Other aspects are the same as specific embodiment 9.

[0051] The following examples are used to verify the beneficial effects of the present invention:

[0052] Embodiment 1:

[0053] A method for preparing a catalytic film based on single-atom iron-manganese oxide is carried out according to the following steps:

[0054] 1. Dissolve polyvinyl alcohol in ultrapure water at a temperature of 75°C and a rotation speed of 150 rpm, add Al2O3, TiO2 and a dispersant to the polyvinyl alcohol solution, then ball mill for 4 hours at a ball-to-material mass ratio of 1:0.25 and a rotation speed of 150 rpm, and finally vacuum degas for 15 minutes to obtain a casting solution;

[0055] The mass ratio of the polyvinyl alcohol to ultrapure water is 1:30; the mass ratio of the polyvinyl alcohol to Al2O3 is 1:50; the mass ratio of the polyvinyl alcohol to TiO2 is 1:20; the mass ratio of the polyvinyl alcohol to the dispersant is 1:20;

[0056] The molecular weight of the polyvinyl alcohol is 44.05Mw, the alcoholysis degree is 98.0mol% to 99.0mol%, and the viscosity is 54mPa.s to 66mPa.s; the average particle size of the Al2O3 is 0.3μm; the average particle size of the TiO2 is 300nm; the dispersant is the dispersant DARVANC-N;

[0057] 2. Drop the casting liquid into the pores of the hollow ceramic membrane substrate, and then dry it at a temperature of 50°C for 150 seconds, and then repeat the dropping and drying for 3 times to obtain the ceramic membrane substrate after drop coating;

[0058] The ratio of the drop volume of the casting solution to the inner surface area of ​​the pores of the hollow ceramic membrane substrate is 3 μL:2 mm 2 ;

[0059] The hollow ceramic membrane substrate was purchased from Pingxiang Jiaheng Ceramics Co., Ltd., with a wall thickness of 2 mm, a diameter of 11 mm, a pore diameter of 7 mm, and a length of 100 mm;

[0060] 3. Add potassium ferrocyanide into ultrapure water, and then stir and dissolve at a temperature of 25°C and a rotation speed of 300 rpm for 8 minutes to obtain a potassium ferrocyanide aqueous solution;

[0061] The concentration of the potassium ferrocyanide aqueous solution is 45 mM;

[0062] Fourth, adding manganese acetylacetonate to n-hexane, and then ultrasonicating in a water bath for 25 minutes at a temperature of 45°C and a power of 200W to obtain a manganese acetylacetonate oil phase solution;

[0063] The concentration of the obtained manganese acetylacetonate oil phase solution was 25 mM;

[0064] 5. Under the condition of a shaking table speed of 100 rpm, the ceramic membrane substrate after drop coating is immersed in a potassium ferrocyanide aqueous solution for 60 minutes, and then taken out to obtain a ceramic membrane substrate after water phase treatment, and the acetylacetone manganese oil phase solution is added dropwise into the pores of the ceramic membrane substrate after water phase treatment, and the interface synthesis reaction is carried out for 45 minutes under the condition of a shaking table speed of 150 rpm, and then dried at a temperature of 60°C for 3 hours to obtain a ceramic membrane substrate after water phase and oil phase treatment, and the ceramic membrane substrate after water phase and oil phase treatment is heated to 600°C at a rate of 10°C / min under a nitrogen atmosphere, and then calcined at a temperature of 600°C for 2 hours, and finally naturally cooled to room temperature to obtain a single-atom iron-manganese oxide catalytic membrane, that is, a hollow ceramic catalytic membrane;

[0065] The ratio of the added volume of the acetylacetonate oil phase solution to the area of ​​the inner surface of the pores of the hollow ceramic membrane substrate is 4 μL:2 mm 2 .

[0066] Comparative Experiment 1: The difference between this comparative experiment and Example 1 is that the average particle size of Al2O3 described in step 1 is 9 μm. The rest is the same as Example 1.

[0067] Comparative Experiment 2: This comparative experiment is different from Example 1 in that: in step 5, the porous ceramic substrate treated with water phase and oil phase is heated to 800°C at a rate of 10°C / min under a nitrogen atmosphere, and then calcined at 800°C for 2h. The rest is the same as Example 1.

[0068] Figure 1 The schematic diagram of the formation of an iron-manganese Prussian blue analog precursor by interfacial polymerization of the catalytic membrane in Example 1. An iron-manganese Prussian blue analog thin film tightly attached to the inner side of the hollow ceramic membrane is formed by an interfacial polymerization reaction between a potassium ferrocyanide aqueous solution and a manganese acetylacetonate oil solution. An Fe-Mn Prussian blue-like thin film with a Prussian blue-like structure is constructed on the surface of the ceramic membrane substrate by interfacial deposition. Its unique Fe-C≡N-Mn structure contributes to the uniform dispersion of Fe and Mn atoms.

[0069] Figure 3 This is a physical picture of the single-atom iron-manganese oxide catalytic membrane prepared in step 5 of Example 1. A single-atom iron-manganese oxide catalytic layer is deposited inside the hollow ceramic membrane, and the catalytic layer activates permonosulfate (PMS) to degrade F-53B through an advanced oxidation process.

[0070] Figure 4 The following are SEM images, (a) is the ceramic membrane substrate after drop coating prepared in step 2 of Example 1, (b) is a partial enlarged view of (a), (c) is a catalytic membrane based on single-atom iron-manganese oxide prepared in step 5 of Example 1, and (d) is a partial enlarged view of (c). As shown in Figures (a) and (b), the hollow ceramic membrane substrate is a nanoporous structure with high porosity. As shown in Figures (c) and (d), the dense Fe-Mn Prussian blue film forms a nanoporous structure due to the phase transformation and shrinkage of the grains during the sintering process.

[0071] Figure 5 The XRD patterns of the single-atom iron-manganese oxide catalyst films prepared in Example 1 and Comparative Experiment 2 are shown in the figure. As can be seen from the figure, when calcined at 600℃ and 800℃ respectively, the catalyst film precursors both obtained (FeO) 0.099 (MnO) 0.901 However, compared with 600℃, the material calcined at 800℃ contains carbides and nitrides with higher strength, while (FeO) 0.099 (MnO) 0.901 The strength is relatively low, so it can be seen that the material fired at 600℃ is more effective.

[0072] Figure 6 This is a molecular structure diagram of a single-atom iron-manganese oxide catalyst film prepared in step 5 of Example 1. As can be seen from the figure, the iron atom is connected to the oxygen atom, the iron atom is isolated, and the manganese atom surrounds the iron atom. The number of iron atoms: the number of manganese atoms = 1:9. This structure can maximize the utilization efficiency of the iron atom catalytic site.

[0073] Embodiment 2, combined with Figure 2 Specific instructions:

[0074] The short-process chromium plating wastewater treatment was carried out using the single-atom iron-manganese oxide catalytic membrane prepared in Example 1 and Comparative Experiments 1 to 2, specifically in the following steps:

[0075] ① Dissolve the chromium mist inhibitor (F-53B) in ultrapure water and stir for 24 hours to obtain a chromium mist inhibitor mother solution, wherein the concentration of the chromium mist inhibitor mother solution is 50 mg / L; dissolve polyacrylamide (MW molecular weight: 15 million-18 million) in ultrapure water and stir to obtain a polyacrylamide mother solution, wherein the concentration of the polyacrylamide mother solution is 1 g / L;

[0076] ② Dilute the mother liquor of chromium mist inhibitor, then add the mother liquor of polyacrylamide to obtain the water sample to be treated, wherein the concentration of chromium mist inhibitor in the water sample to be treated is 0.1mg / L, and the concentration of polyacrylamide is 10mg / L; put the water sample to be treated into the water tank, and add persulfate (PMS) into the water supply tank through the dosing pump, so that the concentration of PMS in the water sample to be treated is 1mM. During operation, turn on the lifting pump to lift the water sample to be treated into the membrane device provided with a single-atom iron-manganese oxide catalytic membrane, and cross-flow filter under the conditions of a flow rate of 2m / s and a transmembrane pressure difference of 0.2MPa. After passing through the membrane device, part of the concentrated water along the pipeline direction is discharged, and the other part enters the water supply tank for recycling. The water after passing through the membrane in the membrane device perpendicular to the pipeline direction is the outlet water, which is collected by the water collection tank, and the membrane flux data is output by the output device. After the cross-flow filtration is completed, the backwash water is backwashed through the pipeline from the backwash water tank through the backwash pump to backwash the membrane.

[0077] Example 3: This example is different from Example 2 in that the single-atom iron-manganese oxide catalytic membrane prepared in Example 1 is used to treat chromium plating wastewater in a short process, and the addition of polyacrylamide is eliminated in step ②. The rest is the same as Example 2.

[0078] Comparative Experiment 3: The difference between this comparative experiment and Example 2 is that: in step ②, the mother solution of chromium mist inhibitor is diluted, and then polyacrylamide mother solution is added to obtain a water sample to be treated, wherein the concentration of chromium mist inhibitor in the water sample to be treated is 0.1 mg / L, and the concentration of polyacrylamide is 10 mg / L; peroxymonosulfate (PMS) is directly added as an oxidant, and the catalytic reaction is carried out for 80 minutes, and the concentration of PMS in the water sample to be treated is 1 mM, and the use of the catalytic membrane and treatment device based on single-atom iron-manganese oxide is cancelled. The rest is the same as Example 2.

[0079] Comparative Experiment 4: The difference between this comparative experiment and Example 2 is that in step ②, the concentration of PMS in the water sample to be treated is 0 mM, 0.25 mM, 0.5 mM and 1.5 mM. The rest is the same as Example 2.

[0080] Figure 7 This is a comparison chart of the pure water flux of the monatomic iron-manganese oxide catalytic membrane prepared in Example 1 and Comparative Experiment 1 in Example 2 and the PAM retention rate for chromium plating wastewater treatment. As can be seen from the figure, the pure water flux of the catalytic membrane obtained by treating the ceramic membrane substrate with 0.3μmAl2O3 is 260L . m -2 . h -1 . bar -1The PAM rejection rate reaches 92.1%, while the PAM rejection rate of the catalytic membrane obtained by treating the ceramic membrane substrate with 9μmAl2O3 is only 50.8%.

[0081] Figure 8 The figure is a comparison chart of the degradation efficiency of F-53B in chromium plating wastewater treatment based on the single-atom iron-manganese oxide catalytic membrane prepared in Example 1 and Comparative Experiment 2. As can be seen from the figure, the degradation rate of F-53B for the catalytic membrane fired at 600°C reaches 89.7%, and the degradation rate of F-53B for the catalytic membrane fired at 800°C reaches 70.2%.

[0082] Fig. 9 The removal rate comparison chart of the short-process chromium plating wastewater treatment based on the single-atom iron-manganese oxide catalytic membrane prepared in Example 1 for Example 2 and Example 3 and the short-process chromium plating wastewater treatment for comparative experiment 3 is shown. It can be seen from the figure that in comparative experiment 3, the chromium mist inhibitor coexists with PAM and no membrane filtration is performed, and the removal rate is 48.3%, and the removal rate of the chromium mist inhibitor is very low. When the hollow ceramic catalytic membrane is used in Example 2 and Example 3, the removal rates of the single chromium mist inhibitor and the coexistence of the chromium mist inhibitor and PAM are 89.4% and 89.7% respectively. It is proved here that PAM has a great influence on the degradation of F-53B when coexisting. The addition of the membrane filtration device intercepts most of the PAM by the membrane filtration, making the chromium mist inhibitor, so that the degradation is not disturbed, and the degradation rate containing PAM is not much different from the degradation rate without PAM.

[0083] Fig.10 The effects of different concentrations of permonosulfate (PMS) on the degradation efficiency of the catalytic membrane in the treatment of chromium plating wastewater using the hollow ceramic catalytic membrane prepared in Example 1 are shown in Example 2 and Comparative Experiment 4. As can be seen from the figure, when the PMS addition concentration is 0mM, 0.5mM, 1mM, and 1.5mM, the removal rates of F-53B are 9.1%, 40.1%, 55.2%, 89.7%, and 88.3%, respectively, which indicates that the most appropriate setting of the PMS dosage concentration is 1mM; when the PMS dosage is lower than 1mM, the degradation efficiency of the chromium mist inhibitor is low. When the PMS dosage increases to 1.5mM, the degradation rate of the chromium mist inhibitor is slightly lower than the effect when the dosage is 1mM, which may be due to the saturation of PMS adsorption in the catalytic reaction, so the PMS dosage concentration is set to 1mM for the most appropriate.

Claims

1. A method for preparing a catalytic film based on single-atom iron-manganese oxide, characterized in that It is carried out in the following steps:

1. Dissolve polyvinyl alcohol in ultrapure water, add Al2O3, TiO2 and dispersant to the polyvinyl alcohol solution, then ball mill, and finally vacuum degas to obtain a casting solution; 2. dripping the casting liquid into the pores of the hollow ceramic membrane substrate and drying it, and then repeating the dripping and drying to obtain a ceramic membrane substrate after drip coating; 3. dissolving potassium ferrocyanide in ultrapure water to obtain a potassium ferrocyanide aqueous solution; 4. dissolving manganese acetylacetonate in n-hexane to obtain manganese acetylacetonate oil phase solution; 5. Immerse the ceramic membrane substrate after drop coating in a potassium ferrocyanide aqueous solution, then take out the ceramic membrane substrate after water phase treatment, drop the acetylacetonate manganese oil phase solution into the pores of the ceramic membrane substrate after water phase treatment to carry out interfacial synthesis reaction, and then dry to obtain the ceramic membrane substrate after water phase and oil phase treatment, calcine the ceramic membrane substrate after water phase and oil phase treatment under nitrogen protection, and finally naturally cool to room temperature, thus completing the preparation method based on single atom iron-manganese oxide catalytic membrane.

2. A method for preparing a catalytic film based on single-atom iron-manganese oxide according to claim 1, characterized in that The mass ratio of polyvinyl alcohol described in step one to ultrapure water is 1:(20-30); the mass ratio of polyvinyl alcohol described in step one to Al2O3 is 1:(50-60); the mass ratio of polyvinyl alcohol described in step one to TiO2 is 1:(20-30); the mass ratio of polyvinyl alcohol described in step one to dispersant is 1:(15-30).

3. According to the preparation method of a single-atom iron-manganese oxide catalytic film according to claim 1, the particle size of Al2O3 described in step 1 is 0.3μm~5μm; the particle size of TiO2 described in step 1 is 200nm~300nm.

4. The method for preparing a catalytic film based on single-atom iron-manganese oxide according to claim 1, characterized in that In step 1, polyvinyl alcohol is dissolved in ultrapure water at a temperature of 70°C to 80°C and a rotation speed of 100rpm to 200rpm, Al2O3, TiO2 and a dispersant are added to the polyvinyl alcohol solution, and then ball milled for 4h to 5h at a ball-to-material mass ratio of 1:(0.2 to 0.3) and a rotation speed of 100rpm to 200rpm, and finally vacuum degassing for 10min to 20min.

5. The method for preparing a catalytic film based on single-atom iron-manganese oxide according to claim 1, characterized in that In step 2, the casting liquid is dripped into the pores of the hollow ceramic membrane substrate, and then dried at a temperature of 45°C to 55°C for 120s to 180s, and then the dripping and drying are repeated 2 to 3 times; the ratio of the dripping volume of the casting liquid described in step 2 to the area of ​​the inner surface of the pores of the hollow ceramic membrane substrate is (2 to 3) μL: 2mm 2 ; The pore diameter of the hollow ceramic membrane substrate described in step 2 is 5 microns to 8 microns.

6. The method for preparing a catalytic film based on single-atom iron-manganese oxide according to claim 1, characterized in that In step 3, potassium ferrocyanide is added to ultrapure water, and then stirred and dissolved for 5 min to 10 min at a temperature of 20° C. to 30° C. and a rotation speed of 200 pm to 400 rpm to obtain a potassium ferrocyanide aqueous solution; the concentration of the potassium ferrocyanide aqueous solution is 40 mM to 50 mM.

7. The method for preparing a catalytic film based on single-atom iron-manganese oxide according to claim 1, characterized in that In step 4, manganese acetylacetonate is added to n-hexane, and then water bath ultrasonication is performed for 20 min to 30 min at a temperature of 40° C. to 50° C. and a power of 120 W to 240 W to obtain a manganese acetylacetonate oil phase solution; the concentration of the obtained manganese acetylacetonate oil phase solution is 20 mM to 30 mM.

8. The method for preparing a catalytic film based on single-atom iron-manganese oxide according to claim 1, characterized in that In step 5, the ceramic membrane substrate after drop coating is immersed in the potassium ferrocyanide aqueous solution for 30 min to 60 min at a shaking table speed of 150 rpm to 200 rpm, and then the ceramic membrane substrate after water phase treatment is taken out, and the acetylacetone manganese oil phase solution is added dropwise into the pores of the ceramic membrane substrate after water phase treatment, and the interface synthesis reaction is carried out for 30 min to 60 min at a shaking table speed of 100 rpm to 200 rpm, and then dried to obtain the ceramic membrane substrate after water phase and oil phase treatment; the ratio of the drop volume of the acetylacetone manganese oil phase solution described in step 5 to the area of ​​the inner surface of the pores of the hollow ceramic membrane substrate is (3 to 4) μL: 2 mm 2 The calcination in step five is specifically carried out under a nitrogen atmosphere, heating to 500°C to 700°C at a rate of 5°C / min to 10°C / min, and then calcining at a temperature of 500°C to 700°C for 1h to 2h.

9. The use of a catalyst film based on single-atom iron-manganese oxide prepared as claimed in claim 1, characterized in that It is used for the degradation of chloropolyfluoroalkyl ether sulfonates; or in the presence of polyacrylamide, it is used for the degradation of chloropolyfluoroalkyl ether sulfonates.

10. The use of a catalytic film based on a single atom iron-manganese oxide according to claim 9, characterized in that It utilizes cross-flow filtration to generate active species for degradation by activating peroxymonosulfate.

Citation Information

Patent Citations

  • Nitrogen-doped metal carbon-based composite ceramic catalytic membrane as well as preparation method and application thereof

    CN115608403A

  • Preparation method of Prussian blue-like inorganic fine separation membrane based on interface confinement principle

    CN117123060A

  • Preparation method of monatomic-based catalytic ceramic membrane as well as product and application of monatomic-based catalytic ceramic membrane

    CN119056440A

  • KR20240009156A

Cited By

  • Preparation method, product and application of monatomic catalytic membrane

    CN121775916A